Orientasi Perilaku Dominan dalam Praktik Kepemimpinan di Pondok Pesantren - Mohamad Ridwan; Suko Susilo (Indonesian Journal of Humanities and Social Sciences, 2021)
This study discusses leadership practices at the Pondok Pesantren Darussalam Sumbersari Kencong, Kepung Kediri. This study uses a qualitative method with a phenomenological approach based on the phenomenon of the rise of adults returning to learning to read the Qur'an. Data mining techniques used interviews with Islamic boarding school caregivers and several administrators. As reinforcement, the researchers conducted documentation and field observations. The results indicate that the leadership of the Darussalam Islamic Boarding School Sumbersari Kencong Kepung Kediri has a relatively high intensity of attention to people and tends to be oriented towards superior-subordinate relationships. The culture at Darussalam Islamic Boarding School Sumbersari Kencong Kepung Kediri prioritizes taste responsibility. It does not prioritize results as long as it is a blessing so that employees are more ta'dim.